Dukungan Sosial Keluarga Meningkatkan Mobilisasi Pada Pasien Paska Laparatomi Di RSUP Dr. Soeradji Tirtonegoro - Siti Fadlilah; Adi Sucipto; Sumarni Sumarni; Yusup Dwiyanto (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: The aim of the study was to determine the relationship between family social support and mobilization in post-laparotomy patients at Dr. Soeradji Tirtonegoro Klaten. Methods: This study used an analytical survey method with a cross sectional approach. A sample of 30 respondents was taken by accidental sampling. The instrument used is a questionnaire. Bivariate analysis using Spearman Rank. Results: Most of the family social support is in good category, namely 19 respondents (63.3%). The majority of post-laparotomy mobilization was sufficient, as many as 25 respondents (83.3%). The results of the bivariate analysis between family social support and postoperative patient mobilization obtained a p-value of 0.002 with a correlation coefficient of 0.544. Conclusion: There is a significant relationship with a fairly strong level of closeness between family social support and mobilization in post-laparotomy patients.